REPRESENTATION OF THE STRATEGY OF INTERCEPTION BY PITCH VARIATIONS IN POLITICAL DEBATES - Aytan Musa Аllahverdiyeva (Alfred Nobel University Journal of Philology)
The political future of debating candidates is often shaped by the degree of credibility based on argumentative strategies. Today, political argumentation has gained particular relevance, especially due to its psychological impact on voters. In political debates, opponents who possess different political backgrounds employ diverse linguistic and prosodic styles. Through linguistic analysis of selected audio and video materials, we identified several linguistic methods that achieve the objectives of divertissement, competitiveness and personification in political debates, which are the main characteristics of this type of political discourse. The differences between ordinary utterances, remark-utterances, simple overlays of remarks, role exchanges and intentional interruptions are also considered as manipulative means, as we argue that these are deliberate and determined by the speakers’ communicative strategies. We focus particularly on the dialogic nature of televised debates, which in this type of political discourse operates on two-levels: “politician – opponent”, and “politician – audience”. Participants in televised debates use various argumentative strategies to influence both their opponents and voters, often deliberately aiming to discredit their opponents and create a contrasting background for manipulation. For this analysis, we focused on the interception strategy, one of the most commonly used in political debates. In the paper, we examine the speech behavior of Donald Trump and Hillary Clinton as a tool to create their media portrait and personify their political programs. Thus, the article focuses on the strategy of interception and its prosodic realization by means of such non-verbal tools as pitch variations accompanied by deliberate interruptions, remarks, refutations and increasing volume of voice which contribute to argumentation in political debates. In other words, the paper aims at benefiting to identify the role of prosodic means in argumentative political debates. The research methodology involves the code biology approach by applying experimental phonetic and phonological methods. Our analysis reveals that prosody is crucial not only in shaping political discourse but also in reflecting politicians’ viewpoints. We tried to match prosody with argumentation, which contributes to synthesizing naturalness in political speeches. Interruptions disrupt the prosodic structure of the statement and conflict with phonetic signals of role switching, such as high/low pitch or terminal tone variations. Opponents convey confidence through pitch variations: the low pitch is an indicator of assertiveness and certainty, whereas the high pitch suggests uncertainty. High pitch occurs when the new information (rheme) is introduced, while low pitch reflects previously stated information (theme). High pitch can also be a strategy to express emotions or a tool to make the opponent give up and concede the role.